Multinational location strategy - Rugman, Alan M.; Mucchielli, Jean Louis (Research in global strategic management ;, 1998)
This examination of multinational location strategy focuses on the areas of economics, management and policy. It discusses issues such as regionalism and international trade; location patterns, local content rules and foreign direct investment; and, plant location in Eastern European countries.